Muscle injury in rats induces upregulation of inflammatory cytokines in injured muscle and calcitonin gene–related peptide in dorsal root ganglia innervating the injured muscle. Issue 4 (14th July 2016) - Sakuma, Yoshihiro; Miyagi, Masayuki; Inoue, Gen; Ishikawa, Tetsuhiro; Kamoda, Hiroto; Yamauchi, Kazuyo; Orita, Sumihisa; Suzuki, Miyako; Oikawa, Yasuhiro; Inage, Kazuhide; Kubota, Go; Sainoh, Takeshi; et al.
ABSTRACT: Introduction : In this study we evaluated the relationships among the behavioral changes after muscle injury, histological changes, changes in inflammatory cytokines in the injured muscle, and changes in the sensory nervous system innervating the muscle in rats. Methods : We established a model of muscle injury in rats using a dropped weight. Behavior was assessed using the CatWalk system. Subsequently, bilateral gastrocnemius muscles and dorsal root ganglia (DRGs) were resected. Muscles were stained with hematoxylin and eosin, and inflammatory cytokines in injured muscles were assayed. DRGs were immunostained for calcitonin gene–related peptide (CGRP). Results : Changes of behavior and upregulation of inflammatory cytokines in injured muscles subsided within 2 days of injury. Repaired tissue was observed 3 weeks after injury. However, upregulation of CGRP in DRG neurons continued for 2 weeks after injury. Conclusion : These findings may explain in part the pathological mechanism of persistent muscle pain. Muscle Nerve 54 : 776–782, 2016